Ecomorfologia de três espécies de Doradidae (Siluriformes) da planície de inundação do alto rio Paraná, Brasil : relações interespecíficas. - Kirchheim, Pablo Davi (2010)
Ecomorphology can be defined as the branch of ecology that analyses the relationship among morphological characteristics and the various ecological aspects that result from variations in resource usage. In this context, this study aimed to evaluate if the external morphological features demonstrated segregation among Oxydoras eigenmanni, Pterodoras granulosus and Trachydoras paraguayensis, discussing the implications in the resource exploitation. The interspecific patterns analyzed for the three species of Family Doradidae were identified through multivariate analysis. The indexes that contributed to species segregation in the principal component analysis (PCA) were: eye relative area, compression index and body relative height, with positive values, and depression índex, reason aspect of the flow e maxillary barbell relative length, with negative values. T. paraguayensis have larger eyes and a higher and more compressed body, while O. eigenmanni e P. granulosus have more depressed bodies, fin flows with bifurcation tendency and relatively longer barbell, correlating these characteristics to natatory acting and alimentary behavior. In the second axis of PCA, the relative mouth width and the head relative width were correlated with positive values, while the relative area of the breastplate fin and the relative length of the maxillary barbell were correlated with negative values. Therefore, this axis is related with the food capture and locomotion. The general diet pattern of the analyzed species showed that P. granulosus consumed superior vegetables, while the other species showed similarity in the choice of the alimentary items, what framed them in the same trophic category, invertivores. The morphologic patterns of segregation observed for the three species of Doradidae can contribute for the understanding of how philogenetically close species can coexist and respond to the different selective pressures of the environment.